PREVALENCE OF BURNOUT SYNDROME IN PHYSIOTHERAPY STUDENTS IN THE EARLY AND FINAL YEARS - Bueno, Elisa Fernanda de Oliveira; Luiz, Larissa Maria Rodrigues; Pellizzari, Camila Costa de Araujo; da Silva, Joyce Karla Machado (Seven Editora, 2025)
Introduction: Burnout Syndrome (BS) is an emotional disorder caused by extreme stress at work and characterized by exhaustion, depersonalization, and feelings of incompetence. BS is increasingly observed in higher education academics, especially in the health area, due to the high curricular requirements and contact with patients. Objective: To analyze the prevalence of Burnout Syndrome among students in the initial and final years of the Physical Therapy course at the State University of Northern Paraná. Methods: A cross-sectional study was carried out in which 102 students from the 2nd to the 8th period of the Physical Therapy course were recruited. Using the Maslach Burnout Inventory Student Survey (MBI-SS), the suggestion to the syndrome among students was analyzed. Results: Burnout Syndrome was more evident among the initial years of the course, and the Emotional Exhaustion (EE) dimension was the most prevalent among students of all years. The highest response rate occurred between the initial years, and most of the volunteers were female. Final considerations: It was possible to observe that students in the early years were more suggestive of Burnout Syndrome when compared to the final years. However, the results show the need to pay attention to the mental health of students, from the first years of the course. DOI: https://doi.org/10.56238/sevened2024.037-220